Organic rankine cycle (ORC) system applications for solar energy: Recent technological advances - Mahlia T.M.I.; Syaheed H.; Abas A.E.Pg.; Kusumo F.; Shamsuddin A.H.; Ong H.C.; Bilad M.R. (MDPI AG, 2023)
Fossil fuels; Publishing; Rankine cycle; Reflection; Solar energy; Temperature; Towers; Linear fresnel reflector (LFR); Organic Rankine cycles; Parabolic dishes; Parabolic trough; Solar towers; Patents and inventions